2015
DOI: 10.1007/s00264-015-2680-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-E diffused highly cross-linked polyethylene liner compared to standard liners in total hip arthroplasty. A randomized, controlled trial

Abstract: In this prospective, randomized, controlled trial on a new vitamin-E diffused HXLPE liner we found, compared to a conventional HXLPE liner, lower initial head penetration and lower superior and medial wear. A longer follow-up than two years is necessary to demonstrate lower overall head penetration in vitamin-E liners compared to contemporary highly cross-linked PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 15 publications
1
62
0
2
Order By: Relevance
“…Only a RCT has been conducted [ 51 ] to compare the wear properties of VE-diffused UHMWPE liner (E1™, Biomet, Table 1 ) with those of highly cross-linked UHMWPE liner (Marathon™, Depuy) articulating with the same 32 mm cobalt-chrome head. Femoral head penetration in the medial/lateral and vertical directions was significantly lower for VE-diffused UHMWPE liners up to two-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Only a RCT has been conducted [ 51 ] to compare the wear properties of VE-diffused UHMWPE liner (E1™, Biomet, Table 1 ) with those of highly cross-linked UHMWPE liner (Marathon™, Depuy) articulating with the same 32 mm cobalt-chrome head. Femoral head penetration in the medial/lateral and vertical directions was significantly lower for VE-diffused UHMWPE liners up to two-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Prospective studies at two to three years follow-up demonstrated no significant differences in femoral head penetration rates between vitamin E doped and virgin highly crosslinked liners [ 150 , 151 , 152 ].…”
Section: 2nd Generation Highly Crosslinked Polyethylenementioning
confidence: 99%
“…Hence, the clinical need to increase the lifespan of THA to 20 to 30 years have led to the development of additional “second‐generation HXLPE” so as to reduce wearing using a method other than irradiation . To reduce the production of wear particles and improve wear resistance, it is important to understand the tribology of the natural synovial joints and the role of lubrication.…”
mentioning
confidence: 99%